Association between age and efficacy of first-line immunotherapy-based combination therapies for mRCC: a meta-analysis - Yanagisawa, Takafumi; Quhal, Fahad; Kawada, Tatsushi; Bekku, Kensuke; Laukhtina, Ekaterina; Rajwa, Pawel; Deimling, Markus von; Chlosta, Marcin; Pradere, Benjamin; Karakiewicz, Pierre I; Mori, Keiichiro; Kimura, Takahiro; et al. (Immunotherapy, 2023)
Aim: To compare the efficacy of first-line immune checkpoint inhibitor (ICI)-based combinations in metastatic renal cell carcinoma (mRCC) patients stratified by chronological age. Methods: According to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, hazard ratios for overall survival (OS) from randomized controlled trials were synthesized. Results: Five RCTs were eligible for meta-analyses. ICI-based combinations significantly improved OS compared with sunitinib alone, both in younger (<65 years) and older (≥65 years) patients, whereas the OS benefit was significantly better in younger patients (p = 0.007). ICI-based combinations did not improve OS in patients aged ≥75 years. Treatment rankings showed age-related differential recommendations regarding improved OS. Conclusion: OS benefit from first-line ICI-based combinations was significantly greater in younger patients. Age-related differences could help enrich shared decision-making.
Keywords: inhibitory kontrolních bodů; Immunotherapy; renal cell carcinoma; Carcinoma, Renal Cell; nádory ledvin; imunoterapie; Sunitinib; karcinom z renálních buněk; Humans; age; tyrosine kinase inhibitors; ICI; immune checkpoint inhibitors; metastasis; Immune Checkpoint Inhibitors; sunitinib; Kidney Neoplasms; lidé